HYPOCENTER DISTRIBUTION ANALYSIS OF SINABUNG VOLCANO ERUPTION IN 2021 USING GEIGER'S WITH ADAPTIVE DAMPING (GAD) METHOD - Arisalwadi, Meidi; Rahmania, Rahmania; Hamidah, Hamidah; Sastrawan, Febrian Dedi; Basuki, Ahmad (Indonesian Physical Review, 2024)
Sinabung Volcano is located in the Karo Highlands, Karo Regency, North Sumatra, Indonesia, with a peak of 2460 meters above sea level. This volcano experienced an increase in volcanic activity in the April-October 2021 period, so it is necessary to analyse volcanic seismicity to determine the hypocenter distribution of the volcano. This study aims to determine the hypocenter distribution and classification of volcanic earthquake types based on seismogram recording data of Sinabung Volcano at four stations, namely LKW, BGR, MDD and SGR stations. The method used in this research is Geiger's method with adaptive damping (GAD) to determine the distribution of hypocenters. The results showed that the hypocenter distribution gathered below the crater centre with depths from 0.172 km to 7.139 km. The determination of the hypocenter distribution of volcanic earthquakes is expected to provide information on the depth of the earthquake to determine the movement of magma and the characteristics of events that occur during the pre-eruption process of Sinabung Volcano so that this data can be used for mitigation decision making when there is an increase in the activity of Sinabung Volcano.